Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jmedchem.5b01679
|View full text |Cite
|
Sign up to set email alerts
|

Design of Ionizable Lipids To Overcome the Limiting Step of Endosomal Escape: Application in the Intracellular Delivery of mRNA, DNA, and siRNA

Abstract: The intracellular delivery of nucleic acid molecules is a complex process involving several distinct steps; among these the endosomal escape appeared to be of particular importance for an efficient protein production (or inhibition) into host cells. In the present study, a new series of ionizable vectors, derived from naturally occurring aminoglycoside tobramycin, was prepared using improved synthetic procedures that allow structural variations on the linker and hydrophobic domain levels. Complexes formed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 46 publications
(82 reference statements)
0
61
0
1
Order By: Relevance
“…Those that have emerged are largely inspired by or directly repurposed from DNA and siRNA delivery methods. However, multiple groups have observed that directly adapting DNA or siRNA vehicles to mRNA delivery can be ineffective, and in those cases it has been suggested that insufficient mRNA release from the carrier likely contributes to the observed failed or inefficient delivery (19)(20)(21)(22)(23). Nonetheless, there have been encouraging preliminary results of recent and ongoing clinical trials using mRNA, underscoring the rapidly emerging importance of mRNA therapeutics in the treatment or prevention of a range of diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those that have emerged are largely inspired by or directly repurposed from DNA and siRNA delivery methods. However, multiple groups have observed that directly adapting DNA or siRNA vehicles to mRNA delivery can be ineffective, and in those cases it has been suggested that insufficient mRNA release from the carrier likely contributes to the observed failed or inefficient delivery (19)(20)(21)(22)(23). Nonetheless, there have been encouraging preliminary results of recent and ongoing clinical trials using mRNA, underscoring the rapidly emerging importance of mRNA therapeutics in the treatment or prevention of a range of diseases.…”
mentioning
confidence: 99%
“…To date, naked, chemically modified, or protamine-complexed mRNA have shown promise in phase I/II cancer trials (24)(25)(26). Recently, preclinical development of materials specific for mRNA delivery has resulted in cationic polymers such as polymethacrylates (27)(28)(29), poly(aspartamides) (30,31), and polypeptides (32), as well as multicomponent cationic lipid or lipid-like formulations (21,(33)(34)(35)(36). In many of these examples, however, transfection efficiencies can be quite low, ranging 20-80% in cells (18), with likely much lower efficiencies in vivo, which requires either high mRNA doses or hydrodynamic injections (32,37).…”
mentioning
confidence: 99%
“…Meanwhile, Habrant et al (2016) synthesized tobramycin-derived lipids using a biodegradable diester linker. A lead lipid was formulated with DOPE at a 1:1 M ratio and showed effective delivery of mRNA, siRNA and DNA in rat and human cell lines (Habrant et al, 2016). Their recently developed paromomycin-based cationic lipids were also used for delivery of these nucleic acid cargos (Colombani et al, 2017).…”
Section: Lipid and Lipid-derived Nanoparticles For Mrna Deliverymentioning
confidence: 99%
“…synthesized a new series of aminoglycoside tobramycin derived ionizable lipids to overcome endosome escape process in mRNA, DNA and siRNA delivery. Compound 30 loaded liposomes containing dioleylsuccinylserinyl‐tobramycin showed the highest transfection efficiency than other compounds that may be due to the presence of ester bond in compound 30 which favored hydrophobic interaction with natural anionic phospholipid and facilitated endosomal escape of all types of nucleic acids . Li et al.…”
Section: Nanocarriersmentioning
confidence: 99%